Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s00535-009-0137-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for complications of endoscopic submucosal dissection in gastric tumors: analysis of 478 lesions

Abstract: This study indicated risk factors for serious complications of ESD. Large resected tumor size was a risk factor for post-operative bleeding, while long operation time was a risk factor for perforation. Information regarding operation risk factors should be useful for planning strategies for ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
147
7
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(174 citation statements)
references
References 39 publications
13
147
7
1
Order By: Relevance
“…In the current study, a procedure time exceeding 115 min was considered to be a reliable marker associated with perforation development by ROC curve analysis. Thus, prolonged procedure time was a highly significant factor for endoscopic perforation; this finding is consistent with those of other studies [9,[11][12][13]16] . However, tumor location was not related to perforation.…”
Section: Clinical Course In Patients With Perforationsupporting
confidence: 92%
See 4 more Smart Citations
“…In the current study, a procedure time exceeding 115 min was considered to be a reliable marker associated with perforation development by ROC curve analysis. Thus, prolonged procedure time was a highly significant factor for endoscopic perforation; this finding is consistent with those of other studies [9,[11][12][13]16] . However, tumor location was not related to perforation.…”
Section: Clinical Course In Patients With Perforationsupporting
confidence: 92%
“…In our previous study [17] , tumor location was also not an independent risk factor for silent free air. Previous studies showed that tumor location (the upper portion of the stomach) was a significant and independent predictor of perforation by multivariate analysis [8][9][10][11][12][13]16,17] . A possible explanation for the discrepancy may be the difference in the number of patients with perforation investigated between ours and other studies.…”
Section: Clinical Course In Patients With Perforationmentioning
confidence: 99%
See 3 more Smart Citations